Article Withdrawal by ASERS Publishing - Fraudulent double submission and legal limitations - Economic Aspects of Human Capital Development in the Context of Renewable Energy - ZHURAVLEV, Pavel; POLTARYKHIN, Andrey; SHARAGIN, Victor; VOROBYEVA, Victoria; BEZVESELNAYA, Zoya; KHODOS, Dmitry (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019DO - 10.14505//jemt.v10.7(39).24, 2020)
The article discusses the economic aspects of human capital development in the context of the use of renewable energy sources. Renewable energy sources are part of alternative energy sources, which also include non-renewable energy resources that are extracted or processed by non-traditional methods. Solar and wind energy are particularly actively developing, from an environmental point of view, the most acceptable and convenient for use in rural areas. Regarding the long-term prospects for the development of renewable energy in the world, there are a large number of diverse forecasts made by various methods, both by research and by government and by international public organizations.